Aspectos práticos e teóricos dos contratos de locação de Shopping Centers - Gonçalves, Lucas Buzaglo (2021)
This work aims to study the practical and theoretical aspects of the lease agreements entered into with shopping centers, as well as the evolution of the mall, tracing its most diverse historical landmarks and its current moment of expansion in Brazil. Given the peculiarities of its architectural design, the mall will be conceptualized. Due to its planning, the concept of tenant mix and its importance will be presented, as well as the most diverse types of customers and the factors that are determinant by the shopping center developer to develop a set of successful shopkeepers to the business. The differentiation of this lease will be addressed in relation to the others, justifying its atypicality due to the Tenant Law and its own characteristics that are not provided for in the legal system. We specify the subjects listed in the composition of the business, provided for in the Tenant Law, as well as their rights and duties based on the complementary documents that make up the shopping center lease agreement. The main principles related to the contract and the in-depth perspective of good faith in the preservation of the business will also be addressed, so that we will bring the influence of the Law on Economic Freedom in the application of the interpretation of the contract. The work also has the scope of discussing the goodwill, the business point, the res sperata and its differentiation from the gloves. As the study progresses, practical questions and the main clauses that can compose the lease will be presented. We will bring a new look at the shopping center regarding e-commerce and the Marketplace developed to increase its profits and modernize the sales of its tenants. And, at the end, we will address the renewal action and its legal aspects required by the Tenant Law